Compartmentation of phosphoglycerate kinase in Trypanosoma brucei plays a critical role in parasite energy metabolism - Blattner, Judith (National Academy of Sciences, 1998)
African trypanosomes compartmentalize glycolysis in a microbody, the glycosome. When growing in the mammalian bloodstream, trypanosomes contain only a rudimentary mitochondrion, and the first seven glycolytic enzymes, including phosphoglycerate kinase, are located in the glycosome. Procyclic trypanosomes, growing in the gut of tsetse flies, possess a fully developed mitochondrion that is active in oxidative phosphorylation. The first six glycolytic enzymes are still glycosomal, but phosphoglycerate kinase is now found in the cytosol. We demonstrate here that bloodstream trypanosomes are killed by expression of cytosolic phosphoglycerate kinase. The toxicity depends on both enzyme activity and cytosolic location. One possible explanation is that cytosolic phosphoglycerate kinase creates an ATP-generating shunt in the cytosol, thus preventing full ATP regeneration in the glycosome and ultimately inhibiting the first, ATP-consuming, steps of glycolysis.